Numerical Modeling of Flow Field in Morning Glory Spillways and Determining Rating Curve at Different Flow Rates - Mohammad Reza Enjilzadeh; Ebrahim Nohani (Salehan Institute of Higher Education, 2016)
Morning glory spillways with drop inlets are normally employed in dams built on narrow valleys or placed on steep slopes. In Iran, morning glory spillways have been commonly used in large Dam projects such as Sefidrood dam, Alborz dam, and Haraz dam. Physical models should be built to accurately determine hydraulic parameters of the flow and flow field in spillways. Establishment of a physical model involves extravagant costs and conditions that cannot be justified in some cases. Therefore, suitable numerical models can be proposed for such circumstances. Using FLOW3D numerical models, 3-dimensional numerical modelling of the flow was calibrated and validated by experimental information associated with morning glory spillway of Alborz dam and accuracy of numerical modelling was determined by relative error of numerical model. So it was attempted to determine flow pattern and control conditions of morning glory spillways in different modes using boundary conditions, inlet conditions and grid spacing of flow field and project rating curve of morning glory spillways. According to the results of numerical model, relative error of numerical modelling equals 6.4% for calculating discharge rate of the spillways. Numerical modelling error is 7.6% for determining depth parameter of the flow in spillway crest in comparison with experimental results.